Reduction of hysteresis in (La1-xCex) y(MnzFe11.4-z)Si1.6 magnetocaloric compounds for cryogenic magnetic refrigeration. (November 2021) - Lai, Jiawei; Sepehri-Amin, H.; Tang, Xin; Li, J.; Matsushita, Y.; Ohkubo, T.; Saito, A.T.; Hono, K.
Abstract: (La, Ce)(Mn, Fe, Si)13 -based compounds which show a giant magnetocaloric effect are potential materials for the cryogenic magnetic refrigeration. However, large hysteresis originating from the first order magneto-elastic phase transition deteriorates cyclic performance of these materials, hindering their practical applications. In this work, Curie temperature of (La1- x Ce x ) y (Mn z Fe11.4- z )Si1.6 compounds was tuned to the cryogenic temperatures below 77 K and hysteresis was successfully reduced to 1.5 K by tuning first order magneto-elastic transition to the critical point of second order magnetic phase transition. Based on detail microstructure characterizations, the reason for the reduction of hysteresis is ascribed to the change of a secondary phase from a paramagnetic LaFeSi phase to ferromagnetic Ce2 Fe17 and α -Fe phases. Cryogenic Lorentz microscopy observations and micromagnetic simulations showed the α -Fe ferromagnetic phase produces a large stray field of ∼0.7 T at their interface. This causes the magnetic field assisted paramagnetic/ferromagnetic phase transition in the NaZn13 -type phase. Cryogenic X-ray diffraction analysis indicated the energy barrier of magneto-elastic transition was reduced, resulting in an enhancement of their mechanical stability during the cyclic performance. This work has shown that the hysteresis in the magnetocaloric materials with first order magneto-elastic transition can be tuned by engineering the size, distribution, and magnetism of the secondary phases. Graphical abstract: Image, graphical abstract